2004
DOI: 10.1177/030802260406700103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning: How do Pragmatic Reasoning, Worldview and Client-Centredness Fit?

Abstract: Using both clinical reasoning data and literature from the past 20 years, this paper sought to examine the relationship between client-centred practice and clinical reasoning, to explore the concept of pragmatic reasoning and to present a diagrammatic conceptualisation of our knowledge of clinical reasoning in occupational therapy. The clinical reasoning literature published between 1982 and 2001 was reviewed and this information was combined with the findings from a study which used a head-mounted video camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 40 publications
3
44
0
4
Order By: Relevance
“…Though more difficult to extrapolate, participants evaluated A SECRET strategies to determine if they were fair to the client in question or the other children within the case scenario. Unsworth (2004) concluded that participants' (occupational therapists) personal motivations, values and beliefs influenced their clinical reasoning within pragmatic reasoning. In another study, Hooper (1997) reported that occupational therapists' worldviews influence how therapists reasoned through clinical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Though more difficult to extrapolate, participants evaluated A SECRET strategies to determine if they were fair to the client in question or the other children within the case scenario. Unsworth (2004) concluded that participants' (occupational therapists) personal motivations, values and beliefs influenced their clinical reasoning within pragmatic reasoning. In another study, Hooper (1997) reported that occupational therapists' worldviews influence how therapists reasoned through clinical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 This idea of ethnography, which developed particularly during the 1970s, is used to collect a large quantity of data within a limited time, when it is coupled with video, thus facilitating the observer's work.…”
Section: The Ethnographic Approachmentioning
confidence: 99%
“…Therefore, according to Unsworth, "focused ethnography is an ideal method to study clinical reasoning, given the emphasis on understanding what participants think that they are doing and why they are doing it." 32 The use of video is a core feature of methods used to investigate clinical reasoning in an authentic setting (i.e., actual clinical environments where physicians manage patients in their everyday practice). According to Wears and Schubert, 30 "Video-reflexive ethnography is particularly well suited to illuminate the intricate relationships that emerge in the context of interprofessional clinical work.…”
Section: The Ethnographic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no accepted definition of expertise, we developed a list of selection criteria (Table 1) [23,30,31]. We sought diversity in our sample [32].…”
Section: Participantsmentioning
confidence: 99%